Teacher perceptions of teacher effectiveness among Indian secondary school teachers of different religious persuasions in northern Natal - Jaggan, Vijay Jaggan (My University, 2015)
R e s e a r c h i n t o e f f e c t i v , t e a c h - n o i s an o n g o i n g p r o c e s s , w i t h r e s e a r c h e r s t r y i n g t o i s o l a t e i n d i c a t o r = o f e f f e c t i v e t e a c h i n g i n t h e i r s e a r c h * o r t h e " i d e a l " t e a c h e r . T h i s s t u d y f o c u s e d on t h e t e a c h e r s ' p e r f e c t i o n s o f t e a c h e r e f f e c t i v e n e s s . I t wa s c o n f i n e d t o q u o t a s a m p l e s o f I n d i a n t e a c h e r s o f t h e H i n d u , M u s l i m a n d - . n r i s t i a n r e l i g i o u s p e r s u a s i o n s i n N o r t h e r n N a t a l . S i n c e t h e I n d i a n t e a c h e r s h a v e s u c h d i v e r s e r e l i g i o u s a n d c u l t u r a l b a c k g r o u n d s . i t wa s a s s ume d t h a t t h i s w o u l d i m p i n g e upon t h e i r n o t i o n s o f t e a c h e r e f f e c t i v e n e s s . T h e p u r p o s e o f t h i s r e s e a r c h t h e r e ' , r e wa s t o i l l u m i n a t e t h e d i f f e r e n t p e r c e p t i o n s o f e f f e c t i v e t e a c h i n g t h a t m a - e x i s t among t h e I n d i a n t e a c h e r s o f d i f f e r e n t r e l i g i o u s a f f i l i a t i o n s and c o n t r i b u t e t o t h e s e a r c h f o r " i d e a l " t e a c h e r . An o p e n - e n d e d . f r e e - r e s p o n s e q u e s t i o n n a i r e wa s a d m i n i s t e r e d t o t h e t e a c h e r s , and t h e t h e me s g e n e r a t e d b y t hem w e r e a g g r e g a t e d . T he r e s u l t s o f t h e s t u d y i ' ' i r a t e t h a t t h e r e i s no d i f f e r e n c e b e t w e e n t h e H i n d u s , M u s l i m and C h r i s t i a n t e a c h e r s a nd t h e i r p e r c e p t i o n s o f w h a t ma k e s a " g o o d " t e a c h e r . F u r t h e r , t h e i r v i e w s o f w h a t ma k e s an e f f e c t i v e t e a c h e r a r e c o m m e n s u r a t e w i t h i n t e r n a t i o n a 1 we s t e r n l i t e r a t u r e . The r e s u l t s , t h e r e f o r e , d e m o n s t r a t e t h a t t h e e t h n i c a nd c u l t u r a l r e a s o n s a d v o c a t e d f o r s e p a r a t e e d u c a t i o n i n S o u t h h : i • i c a a r e f a l l a c i o u s .
A Dissertation submitted to the faculty of Education, University of the Witwatersrand, Johannesburg, in partial fulfilment for the Degree of Master of Education Johannesburg, June 1987